Screenwriting: A Strategy for the Improvement of Writing Instructional Practices - Hernán Amado (Universidad Nacional de Colombia, 2010)
This article presents a pedagogical experience that addresses the use of an instructional strategy called screenwriting aimed at improving the teaching of writing in an educational context. This pedagogical intervention took place in a private English language school, where three adult students willingly participated to create their own short scripts. The idea was to introduce and reinforce the importance of screenwriting to observe its usefulness in education. Students participated in writing workshops for a 3-month period. The workshops included the respective screenwriting theory and activities that helped them to achieve completion of their final stories. Students' final pieces proved that the writing instructional practices were enriching and beneficial.